PROPOSALS AND RECOMMENDATIONS FOR OPTIMIZATION OF THE PROGRAM OF STATE GUARANTEES FОR FREE MEDICAL CARE FOR RUSSIAN CITIZENS - D. V. Fedyaev; D. V. Lukyantseva; V. I. Ignatyeva (IRBIS LLC, 2017)
The article describes questions of medical care regulation and possibility using the mechanisms of concretization for formation of State Guarantees fоr free Medical care for Russian Citizen. The proposed approaches are aimed at the formation of a new system of documentary maintenance of the health system. Inclusion in regulations of mechanisms of concretization allow to control volume, financial resources, quality and availability of medical care.